2019
DOI: 10.1101/708016
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Neural Taskonomy: Inferring the Similarity of Task-Derived Representations from Brain Activity

Abstract: Convolutional neural networks (CNNs) trained for object recognition have been widely used to account for visually-driven neural responses in both the human and primate brains. However, because of the generality and complexity of the task of object classification, it is often difficult to make precise inferences about neural information processing using CNN representations from object classification despite the fact that these representations are effective for predicting brain activity. To better understand und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 19 publications
(10 reference statements)
1
22
1
Order By: Relevance
“…The availability of NSD thus opens the door to using brain activity to directly guide the optimization of deep neural networks. Brain-optimized networks (Seeliger et al, 2021) are a useful alternative to task-optimized networks (Khaligh-Razavi and Kriegeskorte, 2014; Yamins et al, 2014), as the narrowly defined tasks that such networks are typically trained to solve do not necessarily respect the diversity of functions supported by the human visual system (Wang et al, 2019) nor necessarily match properties found in biological visual systems (Sinz et al, 2019). In this regard, NSD is a resource that will contribute to a virtuous cycle of competition between models derived from biological and artificial intelligence.…”
Section: Resultsmentioning
confidence: 99%
“…The availability of NSD thus opens the door to using brain activity to directly guide the optimization of deep neural networks. Brain-optimized networks (Seeliger et al, 2021) are a useful alternative to task-optimized networks (Khaligh-Razavi and Kriegeskorte, 2014; Yamins et al, 2014), as the narrowly defined tasks that such networks are typically trained to solve do not necessarily respect the diversity of functions supported by the human visual system (Wang et al, 2019) nor necessarily match properties found in biological visual systems (Sinz et al, 2019). In this regard, NSD is a resource that will contribute to a virtuous cycle of competition between models derived from biological and artificial intelligence.…”
Section: Resultsmentioning
confidence: 99%
“…Our study provides a systematic and comprehensive picture of human brain functions using DNNs trained on different tasks. Previous studies 3,4,6,7,17-21 have compared model performance in explaining brain activity, but were limited to a few preselected regions and models, or had a different goal (comparing task structure) 22 . We Figure 2b).…”
Section: Discussionmentioning
confidence: 99%
“…Our study provides a systematic and comprehensive picture of human brain functions using DNNs trained on different tasks. Previous studies 3,4,6,7,17–21 have compared model performance in explaining brain activity, but were limited to a few preselected regions and models, or had a different goal (comparing task structure) 22 . We go beyond these efforts by comparing fMRI responses across the whole visual brain using a larger set of DNNs, providing a comprehensive account of the function of human visual brain regions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Key to the engineering of Taskonomy is the use of an encoder-decoder design in which only the construction of the decoder varies across tasks. While recent analyses using a similar approach in human visual cortex with fMRI data [52] have tended to focus only on the latent space of each task's encoder, we choose to extract representations across all layers, better situating Taskonomy within the same empirical paradigm that has so far defined the modeling of object recognition in the primate brain.…”
Section: Neural Taskonomymentioning
confidence: 99%